Updating External Ventricular Drainage Care and Intrahospital Transport Practices at a Community Hospital. Issue 6 (December 2020) - Eigsti, Janice E.
Abstract : ABSTRACT: BACKGROUND: Frontline neurointensive care nurses from 1 community hospital were invited to assess the current state of care related to use of external ventricular drains (EVDs) and intrahospital transport (IHT) policies, investigate and plan practice changes, and implement skills review for nurses caring for the adult patient with an acute brain injury. PROJECT: Our team researched best practices related to EVD care and IHT procedures, updated current EVD insertion checklists, developed nurse role cards to assist with EVD insertion at the bedside, revised current EVD care policies and procedures, and created a new IHT policy. The same nurses shared updated information and skills review for neuroscience nurse peers. CONCLUSION: The goals for the project were met, and practice variation is being reduced. Abstract : Supplemental digital content is available in the text.